Psychotherapy Impact of Infant Breastfeeding Practice Pattern Among HIV Positive Nursing Mothers in Zing Local Government Area, Taraba State, Nigeria: A Systematic Review (Eurasian Medical Research Periodical, 2022)
Breastfeeding, also known as nursing, is the process of feeding an infant directly from the breast or by expressing milk from the breast and delivering it to the infant via a bottle. Based on the results of a sentinel survey, Taraba State has one of the highest HIV/AIDS prevalence rates in North Eastern Nigeria, with 5,500 infected nursing mothers on ART. The goal of this study is to look at Infant Breastfeeding Practice Patterns among HIV Positive Nursing Mothers in Taraba State Zing Local Government Area, Nigeria. The information gathered through a standardized questionnaire was evaluated. To answer the study questions, descriptive statistics methods were used. The disparity in HIV nursing mothers' knowledge and practice of exclusive breastfeeding could be due to the content taught at ANC in different health facilities. 200 HIV nursing mothers reported being influenced on infant feeding option by: ANC staff 60(30%), husband 69(34.5%), Counselor 22(11%), neighbor 19(9.5%), relative 14(7%), and self-decision 16(8%). HIV nursing mothers were asked if Exclusive Breastfeeding has longer term health benefits for the mother and child. A total of 143(71.5%) strongly agreed, 38(19%) agreed, 15(7.5%) disagreed and 4(2%) strongly disagreed. The researchers discovered that HIVpositive nursing mothers in Taraba State Zing Local Government Area practice exclusive breastfeeding because they think it protects their children from common illnesses like diarrhea and pneumonia and is beneficial to both the mother and the child's health. As a result, the researchers recommended that: a well-trained health care professional might encourage HIV nursing moms to breastfeed exclusively. Stakeholders in the health sector should reinforce health facilities and communities through community strategies to increase exclusive breastfeeding practice patterns among HIV positive nursing mothers during ANC and PNC, according to the study. Mothers should also be taught how to extract breast milk and use heattreated or infant formula or wet breastfeeding to feed their babies.